Assistance of digital information systems to improve learning quality in vocational students - Nur Janah; Aldo Setiawan; Helena Anggraeni Putri; Deny Hadi Siswanto (Universitas Pendidikan Indonesia, 2025)
The rapid development of information technology has significantly impacted various sectors of life, including education. This activity was carried out at SMK Muhammadiyah 2 Tempel and involved 28 eleventh-grade students from the Logistics Engineering program. The main objective of the activity was to enhance students' abilities in accessing, understanding, and managing digital information systems to support technology-based learning. The implementation process was divided into three stages: the preparation stage (which involved identifying the needs of both students and teachers), the implementation stage (encompassing workshops, technical training, and intensive mentoring), and the evaluation stage. Data collection techniques included direct observation, semi-structured interviews, and pre-tests and post-tests. The results showed a significant improvement in students' digital skills, as indicated by the increase in the average score. Students became more independent, confident, and active in utilizing digital platforms for learning purposes. Teachers also observed an increase in student engagement and participation during online learning activities. Reflections and feedback from both students and teachers indicated that a participatory approach combined with continuous mentoring proved highly effective in bridging the digital literacy gap. Abstrak Perkembangan teknologi informasi yang pesat telah memberikan dampak yang signifikan terhadap berbagai sektor kehidupan, termasuk pendidikan. Kegiatan ini dilaksanakan di SMK Muhammadiyah 2 Tempel dengan melibatkan 28 peserta didik kelas XI Teknik Logistik. Tujuan utama dari kegiatan ini adalah untuk meningkatkan kemampuan peserta didik dalam mengakses, memahami, dan mengelola sistem informasi digital guna menunjang pembelajaran berbasis teknologi. Proses pelaksanaan kegiatan terbagi menjadi tiga tahap, yaitu tahap persiapan (melalui identifikasi kebutuhan peserta didik dan guru), tahap pelaksanaan (meliputi workshop, pelatihan teknis, serta pendampingan intensif), dan tahap evaluasi. Teknik pengumpulan data yang digunakan antara lain observasi langsung, wawancara semi-terstruktur, serta tes awal (pre-test) dan tes akhir (post-test). Hasil yang diperoleh menunjukkan adanya peningkatan signifikan pada kemampuan digital peserta didik, ditandai dengan kenaikan rata-rata skor. Siswa menjadi lebih mandiri, percaya diri, dan aktif dalam memanfaatkan platform digital untuk pembelajaran. Guru juga mencatat adanya peningkatan keaktifan dan partisipasi siswa dalam kegiatan belajar daring. Refleksi serta umpan balik dari peserta didik dan guru mengindikasikan bahwa pendekatan partisipatif dan pendampingan berkelanjutan sangat efektif menjembatani kesenjangan literasi digital. Kata Kunci: mutu pembelajaran; sekolah menengah kejuruan; sistem informasi digital